Rhythmic Oscillation of Histone Acetylation and Methylation at the Arabidopsis Central Clock Loci - Song, Hae-Ryong (Korea Society for Molecular and Cellular Biology, 2012)
Circadian clock genes are regulated by a transcriptional-translational feedback loop. In Arabidopsis, LATE ELONGATED HYPOCOTYL (LHY) and CIRCADIAN CLOCK ASSOCIATED 1 (CCA1) transcripts are highly expressed in the morning. Translated LHY and CCA1 proteins repress the expression of TIMING OF CAB EXPRESSION 1 (TOC1), which peaks in the evening. TOC1 protein induces expression of LHY and CCA1, forming a negative feedback loop which is believed to constitute the oscillatory mechanism of the clock. The rhythmic oscillation of mouse clock genes mPERIOD 1 (mPER1) and mPER2 has been correlated with regular alteration of chromatin structure through histone acetylation/deacetylation. However, little is known about the relationship between the transcriptional activity of Arabidopsis clock genes and their chromatin status. Here, we report that histone H3 acetylation (H3Ac) and H3 lysine 4 tri-methylation (H3K4me3) levels at LHY, CCA1, and TOC1 are positively correlated with the rhythmic transcript levels of these genes, whereas H3K36me2 level shows a negative correlation. Thus, our study suggests rhythmic transcription of Arabidopsis clock genes might be regulated by rhythmic histone modification, and it provides a platform for future identification of clock-controlling histone modifiers.